Expression and self-assembly of empty virus-like particles of hepatitis E virus. - Li, T C (1997)
Hepatitis E virus (HEV) is a pathogenic agent that causes fecally-orally transmitted acute hepatitis. The genome, a single-stranded positive-sense RNA, encodes three forward open reading frames (ORFs), in which an approximately 2-kb structural protein is located in the 3' end. To produce HEV-like particles the structural protein, with its N terminus truncated (amino acid residues 112 to 660 of ORF2), was expressed in insect Tn5 cells by a recombinant baculovirus. In addition to the primary translation product with a molecular mass of 58 kDa, a large amount of a further-processed molecule with a molecular mass of 50 kDa was generated and efficiently released into the culture medium. Electron microscopic observation of the culture medium revealed that the 50-kDa protein self-assembled to form empty virus-like particles (VLPs). The buoyant density of the VLPs in CsCl was 1.285 g/cm3 and their diameter was 23.7 nm, a little smaller than the 27 nm of native HEV particles secreted into the bile or stools of experimentally infected monkeys. The yield of the VLPs was 1 mg per 10(7) cells as a purified form. The particles possess antigenicity similar to that of authentic HEV particles and, consequently, they appear to be a good antigen for the sensitive detection of HEV-specific immunoglobulin G (IgG) and IgM antibodies. Furthermore, the VLP may be the most promising candidate yet for an HEV vaccine, owing to its potent immunogenicity.